Comunicación multimedia y la interacción digital de los estudiantes de la Carrera de Comunicación Social en la Universidad Técnica de Babahoyo, Extensión Quevedo, año 2019 - Rizo Carmigniani, Evelyn Valeria (2020)
The main idea of this work was the study of the influence of multimedia communication and digital interaction on the students of the social communication career at the Technical University of Babahoyo, Quevedo Extension, so that in this way it does not become a dangerous weapon. in vocational training because there is some dissemination of inappropriate information. T he relationship between multimedia communication and students has been a topic of interest for the different sciences involved in collective social behavior. Multimedia communication today and digital interaction today have become a very influential means of communication in the behavior and development of young people around the world. Currently it is considered important to use these digital tools, which refer to teaching and learning; This has captured the attention of teachers and students due to the fact that it becomes a reinforcement at the time of each chair. That is why, the use and application of the tools mentioned in advance is a didactic method that will accompany the student in their academic training process. Therefore, it is intended to carry out this research, which is as follows, “Multimedia communication and the digital interaction of students in the career of social communication at the Technical University of Babahoyo, Quevedo Extension, 2019.